Perlindungan dan Pemenuhan Hak Asasi Manusia Bagi Pekerja Migran Indonesia di Luar Negeri - Sultoni Fikri (MORALITY: Jurnal Ilmu Hukum, 2022)
Human rights are natural that have been attached to individuals since birth and given directly by God Almighty and as a gift, who has the right to education, health rights, employment rights, and so on. As is known, the dense population of Indonesia, increasing competition, and narrow employment and income are not as expected in addition to the growing daily needs of living, encouraging people to prefer to work abroad commonly referred to as Indonesian Migrant Workers (PMI). The number of cases against Indonesian citizens working abroad who experience various kinds of discriminatory actions. The participation of the state is inseparable from its responsibility to keep protecting its citizens, especially through the government. Monitoring and monitoring (monitoring system) is an action that needs to be appreciated as a form of state concern for its citizens working abroad as Indonesian migrant workers. However, the implementation in practice is not so felt by Indonesian migrant workers. It is this weakness in the system that underlies the author discussing it more deeply. The author uses descriptive qualitative methods by analyzing various mass media platforms to draw on some of the problems that occur in Indonesian migrant workers and associate the causes with rules or legal norms both nationally and internationally (Convention). The results of this study found that on issues related to supervision or monitoring of migrant workers have not been optimal in practice lack of coordination between Indonesian migrant workers and stakeholders both in the destination country as a representative institution, namely the Embassy of the Republic of Indonesia and the Republic of Indonesia.